Explicit solutions of Fisher's equation with three zeros - M. F. K. Abur-Robb (International Journal of Mathematics and Mathematical Sciences)
Explicit traveling wave solutions of Fisher's equation with three simple zeros ut=uxx+u(1−u)(u−a), a∈(0,1), are obtained for the wave speeds C=±2(12−a) suggested by pure analytic considerations. Two types of solutions are obtained: one type is of a permanent wave form whereas the other is not.